Pointed Arch in Islamic Architecture Between Intentional innovation & spontaneous aim - Al - Maliki, Kabila Fares (Iraqi Journal of Architecture and Planning, 2009)
Arch is founded in Islamic Arabic Architecture in many different Buildings, for aethetical and functional purposes that made this Arch one of its symbols, parallel with it, so the study of this Arch is very important. Many studies took care of this arch, pointed arch with four centers that it is Islamic Arab innovation comparative with all other kinds of arches. We don’t know why this arch is specially innovated & used in Islamic Arab Architecture? What its relationship with pointed Arch by two centers? What causes behind this innovation? This study aim to search in many concepts explain the innovation of this pointed Arch (with four centers) analytically to discover the beginnings, causes for its appearance, styles within the unity of Islamic spirit, so it studied Arch Philosophical, its history expressionism, aesthetical values, to be contents of this research to discover its hidden, answering many questions, inquiring about intention of this Arch or its spontaneous ? Was it related to aesthetical values, philosophical, ideological, or others? While pointed Arch with two centers more powerful structurally than pointed Arch with four centers, but it was more important and more employment in Islamic Arab Architecture.